Impact of DEXA-Based Bone Mineral Density Evaluation on Orthopedic Surgical Decision Making - Ahmed Abdullah, Wissam (Journal of Neonatal Surgery, 2025)
Background: Many elderly patients undergoing orthopedic procedures, such as arthroplasty or spinal fusion, often present with compromised bone quality. Dual-energy X-ray absorptiometry (DEXA) measures bone mass and area through a two-dimensional method. Although bone depth is not measured, the dimensions of the bone can influence the observed bone mineral density (BMD). DEXA scans are essential in assessing bone mass density and identifying potential bone-related issues. Method: A prospective cohort study was carried out involving 120 patients who were slated for orthopedic surgery. Participants were selected using convenience sampling from the hospital's orthopedic surgery department. The study aimed to refine the decision-making process for orthopedic surgeries by assessing osteoporosis via dual-energy X-ray absorptiometry (DEXA) examinations. The study cohort was segregated into a control group comprising 40 healthy individuals and two experimental groups, each comprising 40 patients diagnosed with osteoporosis. Results: The analysis of variance (ANOVA) test uses the P value and F value to assess the significance of the results. The results show a decline in bone density among individuals with chronic conditions like heart disease, diabetes, and hypertension. These disorders can directly influence osteoporosis, damaging blood vessel health, impair bone absorption capacity, and compromise the immune system's ability to secrete hormones, including insulin. Obesity and insufficient physical activity also heighten the risk of osteoporosis in individuals with hypertension and diabetes. Conclusion: Incorporating dual-energy X-ray absorptiometry (DEXA) scans into the preoperative evaluations of elderly patients undergoing orthopedic surgery is essential for improving patient outcomes. Identifying those at elevated risk for osteoporosis and related complications allows healthcare professionals to tailor both surgical and medical strategies, thereby enhancing postoperative recovery and optimizing long-term outcomes.